Regional economic cooperation and integration through growth triangles: The case of IMS-GT - Majid, Rahimah (Universitas Islam Riau Indonesia, 2010)
The emergence of growth triangles at the ASEAN level such as the Indonesia-Malaysia-Singapore Growth Triangle (IMS – GT), Indonesia-Malaysia-Thailand Growth Triangle (IMT – GT), and Brunei Darussalam-Indonesia-Malaysia-Philippines Growth Area (BIMP – EAGA) was aimed at promoting faster economic growth through regional economic co-operation and the integration of economic activities among the participating countries. Through growth triangles, differences and similarities in endowments of factor of production and comparative advantages in the participating countries can be exploited to promote external trade and investment. By optimizing the economic complementarities between them would enable the region to attract both domestic and foreign investment and in promoting exports. However, a successful economic cooperation and integration in this growth area requires collaborative efforts and close cooperation among the participating countries - the government as well as the private sector. The extent of mutual benefits also depends upon the degree of exploitation of economic complementarities; geographical proximity, and infrastructure development in those countries. Of the three growth triangles (IMT-GT; BIMP- EAGA; IMS-GT), the IMS-GT is the most successful sub-regional cooperation that has provided economic benefit to the member regions. Singapore being the most developed region acts as the engine of growth in this growth area. Rapid economic growth and industrialization process of Singapore’s economy has increased the needs of Singapore to relocate its labor-intensive industries to low-cost neighbouring countries like Malaysia and Indonesia. These complementarities has developed a strong linkages between Singapore – Riau as well as Singapore – Johor, but however there is not much linkage between Johor – Riau due mainly to the lack of complementarity between these two areas. The positive spillover effects help to promote economic growth in the less developed regions particularly the Riau province – Batam and Bintan Islands.